Pertinencia del plan de manejo y mejoramiento ambiental para la protección en el humedal Thomas Van Der Hammen (2018)
In the analysis of this research project, it is sought to establish the effective and truly effective means to establish the principles, norms and laws that can be established and executed in front of the topics related to the environment and its similes, especially it is focused on the reserve of the Thomas Van Der Hammen wetland, the study of its origins and historical background, the different environmental impacts, variations and damages that it has suffered on the part of human beings and naturally. It is also focused on creating environmental awareness, as stipulated in the Political Constitution of Colombia of 1991, and that with the help of international conventions ratified by Colombia, they have been disseminating and defending with vigor, and promoting policies to guarantee a healthy environment related to the right to life for future generations and since they are a factor of transformation and which are formed in a thought of protection and ecological awareness in favor of existing in relation to our natural environment and respect for the planet and environment.